Glycol chitosan nanoparticles as specialized cancer therapeutic vehicles: Sequential delivery of doxorubicin and Bcl-2 siRNA - Yoon, Hong Yeol; Son, Sejin; Lee, So Jin; You, Dong Gil; Yhee, Ji Young; Park, Jae Hyung; Swierczewska, Maggie; Lee, Seulki; Kwon, Ick Chan; Kim, Sun Hwa; Kim, Kwangmeyung; Pomper, Martin G. (NATURE PUBLISHING GROUP, 2014)
Conventional chemotherapy is plagued with adverse side effects because cancer treatments are subject to numerous variations, most predominantly from drug resistance. Accordingly, multiple or multistage chemotherapeutic regimens are often performed, combining two or more drugs with orthogonal and possibly synergistic mechanisms. In this respect, glycol chitosan (GC)-based nanoparticles (CNPs) serve as an effective platform vehicle that can encapsulate both chemotherapeutics and siRNA to achieve maximal efficacy by overcoming resistance. Herein, DOX-encapsulated CNPs (DOX-CNPs) or Bcl-2 siRNA-encapsulated CNPs (siRNA-CNPs) exhibited similar physicochemical properties, including size, surface properties and pH sensitive behavior, regardless of the different physical features of DOX and Bcl-2 siRNA. We confirmed that the CNP platform applied to two different types of drugs results in similar in vivo biodistribution and pharmacokinetics, enhancing treatment in a dose-dependent fashion.
Keywords: TUMOR-BEARING MICE; DRUG-DELIVERY; EFFICACY; CHEMOTHERAPY; MICROENVIRONMENT; RESISTANCE; CISPLATIN; MODELS; CELLS